Mineração de dados para encontrar características e sintomas em comum entre os pacientes de covid-19 no Brasil - Almeida, Renato Luiz de (Universidade Federal do Tocantins, 2022)
At the end of 2019, a dangerous variant of the covid virus emerged, SARS-CoV-2, the one that causes covid-19. This new virus caused a worldwide pandemic that extends to the present day, it has spread rapidly across the globe causing the contamination of a large part of the population. This pandemic has put us in front of a large number of sick and dead, due to this level of severity, deep damage has arisen in our society, some of which are irreversible. From then on, our lives changed completely, new habits and customs were included in our daily lives, such as social isolation, distancing, stricter personal hygiene, new ways of working, among other things. In this scenario, when we look at computing, we see its great importance to the world, as it plays a great role in combating and understanding the virus that causes covid-19. Focusing on the area of data science, this work aims to find common characteristics and symptoms among patients by applying data mining techniques in cases of covid-19 from all over Brazil.